Local and transnational identity, positionality and knowledge production in Africa and the African diaspora (2022)
How does shared identity between researcher and the researched influence trust-building for data generation and knowledge production? We reflect on this question based on two separate studies conducted by African-based researchers in sociology and political science in Nigeria. We advanced two interrelated positions. The first underscores the limits of national belonging as shorthand for insiderness, while the second argues that when shared national/group identity is tensioned other intersecting positions and relations take prominence. We also show that the researched challenge and resist unequal power relations through interview refusal or by evading issues that the researcher considers important, but the participant perceives as intrusive. We shed light on the vagaries, overlaps, and similarities in the dynamics of belonging and positionality in researching Africans in and outside Africa as home-based researchers. Our contribution advances the understanding of field dynamics in the production of local and cross-border knowledge on Africa/Africans.